Dextran-coated Fe3O4 nanoparticles with ratio-dependent drug loading: structural characterization and cytotoxicity in colorectal cancer cells - Karimova, Aynura; Hajizada, Sabina; Shirinova, Habiba; Nuriyeva, Sevinj; Gahramanli, Lala; Mehdiyeva, Aygun; Eyvazova, Goncha; Sadikhov, Toghrul; Lenz, Natalia; Nasirova, Inji; Reissfelder, Christoph; Yagublu, Vugar (Frontiers in Nanotechnology, 2025)
IntroductionThis study focuses on the development of dextran-coated iron oxide nanoparticles (Fe3O4@Dextran NPs) as carriers for chrysin, a natural flavonoid with recognized anticancer activity.MethodsFe3O4@Dextran NPs were synthesized via co-precipitation and loaded with chrysin at different drug-to-nanoparticle ratios. Structural and physicochemical characterization was performed using X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and Vibrating Sample Magnetometry (VSM). Drug loading efficiency was determined spectrophotometrically. The anticancer efficacy of the drug-loaded samples was assessed in vitro against HCT-116 human colorectal carcinoma cells using the MTT assay, with statistical analysis performed by one-way ANOVA.ResultsXRD revealed an average crystallite size of 17 nm for Fe3O4@Dextran, which decreased to ∼15 nm upon chrysin loading. FTIR confirmed the successful incorporation of chrysin without compromising structural stability. VSM measurements demonstrated superparamagnetic behavior with a saturation magnetization of 69.2 emu/g. Drug loading efficiencies were 42%, 54%, and 57% at drug-to-nanoparticle ratios of 1:0.5, 1:1, and 1:2, respectively, with evidence of saturation at higher concentrations. The Fe3O4@Dextran+D2 formulation exhibited optimal drug loading, maintaining structural integrity and enhanced cytotoxic activity against HCT-116 cells.ConclusionFe3O4@Dextran+D2 demonstrated favorable structural integrity (as evidenced by XRD and FTIR analyses) along with notable anticancer activity against HCT-116 cells. Its performance is attributed to optimal drug loading without surface saturation, supporting its potential as a structurally stable drug delivery system.